1992
DOI: 10.4039/ent124341-2
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF FOOD SOURCES ON THE LONGEVITY AND FECUNDITY OF PHOLETESOR ORNIGIS (WEED) (HYMENOPTERA: BRACONIDAE)

Abstract: Can. Ent. 124: 341-346 (1992) The fecundity of first-generation adult Pholetesor ornigis (Weed) increased when individuals were confined with flowers of creeping "Charlie" (Glechoma hederacea L.), dandelion (Tarmacum oficinale Weber). and apple (Malus domesricus L.), but not with blossoms of chickweed [Stellaria media (L.) Cyril101 or Shepherd's purse [Capsella bursa-pastoris &.) Medic]. Longevity of P. ornigis was little affected. The fecundity of second-generation P. ornigis increased when individuds were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
35
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(46 citation statements)
references
References 16 publications
10
35
0
1
Order By: Relevance
“…Many authors have claimed that the diet of adult parasitoids significantly affects longevity and parasitization ability 8,10,11,15,27,33 . However, practical methods for artificial food supply in commercial greenhouses have not been discussed.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors have claimed that the diet of adult parasitoids significantly affects longevity and parasitization ability 8,10,11,15,27,33 . However, practical methods for artificial food supply in commercial greenhouses have not been discussed.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on food-foraging have been initiated as early as in the 1910s (Howard, 1910;Doten, 1911;Johnston, 1913) but only limited aspects of parasitoid feeding have been documented. In laboratory studies, the availability of a variety of food has been shown to increase longevity and fecundity of parasitoids (Leius, 1961a,b;1963;Syme 1975Syme , 1977Jervis and Kidd, 1986;Hagley and Barber, 1992;Idris and Grafius, 1995;Olson and Nechols, 1995). In some species, feeding was even found to be obligatory before oviposition could take place (Leius, 1961a;Jervis and Kidd, 1986;Takasu and Hirose, 1991).…”
Section: Foraging For Food and Hosts As Influenced By Parasitoids' Inmentioning
confidence: 99%
“…Laboratory studies have demonstrated that parasitoids fed with honey or sugary solutions have their longevity and/or fecundity increased (Syme 1977;Hagley & Barber 1992;Leatemia et al 1995;Siekmann et al 2001;Sisterson & Averill 2002). In the case of C. stephanoderis, laboratory studies demonstrated that diluted honey extends adult survivorship up to 80% (Abraham et al 1990;Barrera et al 1993;Lauzière et al 2000).…”
Section: Discussionmentioning
confidence: 99%